Restart Remote Modem Using SMS and Arduino for First Level Handling - Bakhtiar Rifai; Vito Triantori; Emirotun Nafisah (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
So far many companies still don’t use maximally existing information technology, which in fact this technology is very useful for the company as a means to help employees so that more quickly and responsive when there is a problem. During this time if there is interference on the network is still a manual way of asking the PIC (Person In Charge) to do first level handling example to restart the modem, check wiring or plug unplug it is sometimes difficult to do if the PIC (Person In Charge) Uncooperative, PIC is not available it will cause the duration of handling interruption. To facilitate a handling of the interference then the author will make tools restart the remote modem for first level handling in order to facilitate the work in handling interference and minimize the arrival of technicians just to restart the device. From the description of the problem above, the author found the idea to make a tool restart modem distance ahu. The tool uses Arduino Uno R3 microcontroller. How it works via SMS command to the tool and the tool will cut the current so it can restart the modem automatically